2008
DOI: 10.1016/j.bmc.2008.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Isocoumarin-based inhibitors of pancreatic cholesterol esterase

Abstract: Pancreatic cholesterol esterase (CEase), which is secreted from the exocrine pancreas, is a serine hydrolase that aids in the bile salt-dependent hydrolysis of dietary cholesteryl esters and contributes to the hydrolysis of triglycerides and phospholipids. Additional roles for CEase in intestinal micelle formation and in transport of free cholesterol to the enterocyte have been suggested. There also are studies that point to a pathological role(s) for CEase in the circulation where CEase accumulates in atheros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 20 publications
2
34
0
Order By: Relevance
“…Flavonoids have been reported to irreversibly bind with the cholesterol esterase enzyme in its active fatty acid pocket at Serine 194. It was also suggested that the flavonoids act as suicide substrates ahead of cholesterol esters 23 .…”
Section: Resultsmentioning
confidence: 99%
“…Flavonoids have been reported to irreversibly bind with the cholesterol esterase enzyme in its active fatty acid pocket at Serine 194. It was also suggested that the flavonoids act as suicide substrates ahead of cholesterol esters 23 .…”
Section: Resultsmentioning
confidence: 99%
“…Flavonoids have been reported to irreversibly bind with the cholesterol esterase enzyme in its active fatty acid pocket at Serine 194. It was also suggested that the flavonoids act as suicide substrates ahead of cholesterol esters 23 . The inhibitory effect of the extract against bovine pancreatic cholesterol esterase was performed, which showed good activity and the same was comparable with that of the standard used, Orlistat.…”
Section: Resultsmentioning
confidence: 99%
“…The well-established link between plasma cholesterol levels and coronary artery disease and the contribution of elevated plasma cholesterol, specifically Low Density Lipoprotein (LDL)-cholesterol, to other diseases including cancer, obesity and diabetes, have made control of plasma cholesterol a major health aim [5].…”
Section: Introductionmentioning
confidence: 99%